Target groups assistance or Universal coverage: Georgian pathway to reach the SDGs - Goginashvili, Ketevan (Caucasus Journal of Health Sciences and Public Health, 2019)
Achieving Universal Health Coverage by 2030 is one of the priorities of the UN Sustainable Development Goals (Priority 3.8) and World health Organizations’ Thirteenth general programme of work 2019-2023. From the 1990s, after independence, Georgia has gone through a diverse and interesting way towards achieving universal coverage. A number of reforms were implemented in the healthcare sector: 1995-2003 - introduction of mandatory health insurance (3% + 1%); 2007-2012 - state health insurance through the private insurance companies for target groups and since 2013 - universal access to health services. Comparison of the models of target population coverage by the health service and the universal coverage showed that both stages of healthcare financing system are characterized by the high share of out-of-pocket payments on health care services, especially on drugs (OOP on drugs as share of Total Health Expenditure – 36-40%), and thus a gradual increase in state funding for healthcare should be advocated (recommendation of World Health Organization for middle income countries - 4-5% of GDP and 14-15% of State budget). The need for development of primary health care and preventive services also remains a significant challenge. Introduction of modern systems for quality control and provider remuneration is crucial for the financial sustainability of the healthcare system and cost containment (Diagnisis-retalet Groups, Result based Financing, Active purchasing, Selective contracting). And the state program providing medicines for chronic diseases should be expanded to reduce the cost of pharmaceuticals